Characterisation of Inter Digital Capacitor for water level sensor: article / Noor Aishah Muhammad - Muhammad, Noor Aishah (2010)
Water levels sensors are studied by using Inter Digital Capacitor (IDC) technique on Printed Circuit Board (PCB). The effectiveness of using PCB is studied as to reduce the cost of making sensor. IDC technique is used to make the capacitance measurement of the solution became more effective. This paper reports the effects of width and spacing of the capacitor electrode on capacitance value. This paper also presents simulation and experimental data to characterize the sensor. The result shows that the capacitance value is directly proportional to the electrode’s width and inversely proportional to the electrode’s spacing. When the IDC is tested with different medium i.e. tap water and distilled water, the capacitance value for tap water is much bigger compared to distilled water.